Iberian market entry strategy for a new brand for mattress - Silva, Pedro André Pinho da (2019)
This thesis is studying the possibility of the Eliconfort brand to internationalize for the Iberian market. It currently produces for several brands in Portugal and Spain but does not have its own identity as a brand. As Eliconfort has its own product, process and production knowledge, this is a great opportunity to assert yourself as a brand. Based on previous literature, a conceptual model was proposed and tested that investigates the possibilities of internationalization, the importance of a brand, factors that influence the shopping experience, perceptions, satisfaction and intentions, in the B2C and B2B context. This study provides more information about the concepts. An interview was conducted for 66 individuals in the context of the mattress industry. The research methodology used in this dissertation is qualitative. The results of this investigation reveal that the internationalization of the brand has to be very well studied and worked, since the creation of a strategy of adaptation to the Spanish market, understanding the characteristics of products in each market region and identifying the determining factors to enter the market.